Open Innovation Ecosystems Creating New Value Constellations in the Financial Services - Fasnacht, Daniel (Management for Professionals,, 2018)
Sharing information and knowledge, co-innovating with clients, communities, and competitors and adopting cognitive technology, robo advisors, crowdfunding, and blockchain reflect current socio-economic behaviour. Emerging growth regions in Asia, demographic shifts, intergenerational wealth transfers and increasing regulations are other trends that amplify each other, disrupt the client journey, and affect the entire economy. Moreover, unprecedentedly, new market entrants outside the financial sector, be it Amazon, Apple, Google, or Facebook, are increasingly expanding their scale and scope to offer financial services. Featuring case studies of Chinese business ecosystems, such as Alibaba/Ant Financial, that have transformed from displaying domestic and organic growth to rapid global expansion, this highly readable book gives you glimpses of how banking services are evolving. We break down everything you need to know about the foray of challenger banks into the financial services. You learn how they link health to wealth data and gain advantages through analytical capabilities in the race to attract sophisticated clients with highly personalized experiences. The next level of creating and capturing value for clients and businesses involves platform models embedded in cross-sector ecosystems. Digital platforms are the crucial entry point to global markets, creating value for multiple sides. They leverage self-driving ecosystems that go beyond linear value chains applied in traditional business models as the sources of growth in an interconnected world are collaboration and network effects. The winners will be those who open up and engage themselves in an ecosystem that transcends organizational boundaries and performs without sector borders because every actor contributes to the value constellation of the system. The book provides practitioners and scholars with new insights into open and holistic business models, where competition in future will be between ecosystems rather than at the company level. It encourages leaders to expand their skills and think through the lens of the ecosystem theory while developing compelling strategies to serve the next-generation clients.